Job Satisfaction of the Civil Service Police Unit in Palembang and Malang City - Kurniawati, Rizka; Darmawan, Ahmad Hafizh (Indonesian Journal of Behavioral Studies, 2023)
The civil service police unit is one of the regional government agencies that enforce local regulations and help maintain peace and public order. Each region certainly has different worker criteria, for this reason it is necessary to pay attention to the factors that affect job satisfaction to problems that can be detrimental to an institution. The purpose of this study was to determine the level of job satisfaction among members of the civil service police unit in Palembang and Malang. Research comparative descriptive with quantitative methods. The job satisfaction scale uses a scale the Job Satisfaction Questionnaire (JSQ) with a total of 36 items with a total sample of 120 respondents. Based on the results of statistical analysis, it is known that the value of M = 27.16 for the city of Palembang and M = 28.88 for the city of Malang with the same significance as P = 0.004, which means that there is no significant difference in the level of job satisfaction of members of the civil service police unit Palembang and Malang City.